International agricultural research for food security, poverty reduction, and the environment: What to expect from scaling up CGIAR investments and “Best Bet” programs - von Braun, Joachim; Fan, Shenggen; Meinzen-Dick, Ruth S.; Rosegrant, Mark W.; Nin-Pratt, Alejandro (International Food Policy Research Institute, 2008)
The recent food crisis, combined with the energy crisis and emerging climate-change issues, threatens the livelihoods of millions of poor people as well as the economic, ecological, and political situation in many developing countries. Progress in achieving development goals (such as cutting hunger and poverty in half by 2015) has been delayed significantly; in fact, the number of food-deficient people actually increased in the past two years by at least 75 million. These challenges require multifaceted, science-based technological, economic, and political approaches. Through its international research centers, its publicly available research, its broad network of partnerships, and its long experience in the field, the CGIAR is well positioned to contribute to the global effort to foster food production, increase access to food, and reduce poverty and hunger in both rural and urban areas. However, the system cannot effectively address these global challenges without additional funding and improved organizational design. The latter is being addressed by an ongoing change process. The former is the focus of this paper, which examines what can be expected from a scaled-up CGIAR.